Pendampingan Pengelolaan Usaha Industri Kecil sebagai Peningkatan Ekonomi Masyarakat Kerupuk Rambak Kabupaten Kendal - Yusrinia Afifah (Fakultas Dakwah IAIN Jember, 2022)
One of several UMKM centers in Tegal Regency is the rambak cracker industry center located in Tegal Village, Adiwerna District. The rambak cracker industry center in this village has been able to grow and develop and has great potential to improve the welfare of the community. Local leather is increasingly difficult to obtain due to competition in demand for the leather tanning industry, causing several leather rambak cracker industries to use imported leather as their raw material. Imported leather is imported from Korea and China, from suppliers and wholesalers who are able to import directly from abroad, which generally trade in imported leather is done clandestinely (not done in public markets). The problem that arises is the guarantee of the halalness of imported leather that will be used as rambak crackers, because it is feared that it comes from pork skin or from cow skin that is cut illegally. And also the production in Adiwerna District is still manual and everything Mr. Sutrisno does is still out of date in terms of packaging design and marketing methods. The target community is residents in the Tanjungsari District, Tegal Regency. The first target is the wives of the Village Heads in the Adiwerna District totaling 35 (thirty five) people. This audience is considered a strategic audience in continuing to disseminate knowledge about how to process crackers from cowhide to the community in their respective villages. In this training, under the guidance of the rambak cracker entrepreneur, Mr. Sutrisno, this training and service got a significant increase from the results of improving the economy of the surrounding community and increasing sales in small industrial businesses around the Adiwerna sub-district.